Japan Administered Account for Selected IMF Activities (JSA) : Annual Report for Fiscal Year 2008. (International Monetary Fund, 2008)
This paper reports a brief description of the IMF and its activities, focusing in particular on its technical assistance (TA) activities. The report then describes in greater detail the Japan Administered Account for Selected Fund Activities (JSA)-including its objectives, size, scope, and use, as well as assessments of its activities, with a focus on fiscal year (FY) 2008-and the TA activities and scholarship programs that it finances. The IMF finances technical assistance for its member countries, devoting some 25 percent of its annual operating budget to TA work and training. Although most technical assistance is financed through internal resources, external financing from bilateral and multilateral partners has been increasing over the past few years and constitutes an important pillar. The responsibilities of the Regional Office in Tokyo include collaborative efforts between the IMF and Japan that strengthen economic prospects in the Asia-Pacific region, and also include support of various regional policy forums, such as Asia-Pacific Economic Cooperation, the Association of Southeast Asian Nations, and the Pacific Islands Forum.